OPTIMALISASI PENYELIDIKAN KASUS PENCURIAN KENDARAAN BERMOTOR DALAM MENINGKATKAN PENGUNGKAPAN TINDAK PIDANA DI KOTA PALU - Romy, Romy (Universitas Tadulako, 2021)
Â The research in this thesis is motivated by the observations of researchers on the data of vehicle theft in the city of Palu, which continues to increase every year, even the crime of motor vehicle theft is one of the crimes that often occurs in the city of Palu. As a person directly involved in the process of handling these criminal acts, the author feels he has a great responsibility to think about efforts to optimize the handling of cases of motor vehicle theft. The process in the criminal justice system that begins in the investigation process makes the writer interested in observing and analyzing a model that can be used as an optimization effort, so that quickly and carefully the theft of the motor vehicle can be resolved. For this reason, this study uses sociological or empirical juridical methods. The formulas raised are: 1) What is the Effort to Optimize the Investigation of Motor Vehicle Theft Cases in Palu City? 2). What is the Investigation Model that can reduce the number of cases of Motorized Vehicle Theft in Palu City? The results obtained from this study and answer the problem formulation that the Efforts to Optimize the Investigation of Motor Vehicle Theft Cases in the City of Palu, have not run optimally in accordance with the wishes of law enforcement officials. Internal efforts made in the form of using the Cyber system only apply to tracking the whereabouts of the perpetrators via mobile phones and this is certainly inaccurate because it could be that the perpetrator's position is already in great distance from the vehicle. External efforts are also the elements of related agencies and elements of society to make the need for a lot of time and energy to get information on the whereabouts of the perpetrators and the vehicle of fraud. The Investigation Model that can reduce the number of cases of Motorized Vehicle Theft in Palu City is through a Cyber System called